Safety of MDCK cell culture-based influenza vaccines. (February 2011) - Gregersen, Jens-Peter; Schmitt, Heinz-Josef; Trusheim, Heidi; Brööker, Michael
After more than 60 years, the conventional production of influenza vaccines employing fertilized chicken eggs has reached its limits –– both in terms of temporal flexibility and vaccine production volume. This problem is compounded by the fact that the pandemic-driven situation in 2009 has roughly doubled the overall vaccine demand. Modern cell culture technology has significant advantages over the conventional method of manufacturing influenza vaccines employing embryonated chicken eggs, and enables manufacturers to respond rapidly to the increasing worldwide seasonal and pandemic-driven need for influenza vaccines. Recent articles in the popular press claiming that cell culture-based influenza vaccines can cause tumors have fomented uncertainty among the general population and physicians, and also discredit officially accepted test results and product licensing. This article provides an overview of the safety profile of the cell culture technology, of the cells and of the final vaccine product.